(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2024)
It is known that the process of training drivers is carried out by forming a set of knowledge, skills, habits and qualities that reliably guarantee practical driving of a vehicle. The article presents the analysis of the system of training of motor vehicle drivers in the USA and its uniqueness, as well as the positive experiences achieved in this field. There are also some requirements that must be followed by drivers in order to drive safely on the roads.